Mollifying green skepticism: Effective strategies for inspiring green participation in the hospitality industry - Kim, Eunjin (Anna); Kwon, Eunseon; Hong, Seoyeon; Shoenberger, Heather; Stafford, Marla Royne (Frontiers in Psychology, 2023)
Environmental awareness is a growing concern for consumers, and effective green messaging strategies are crucial for businesses. This 2 × 2 between-subject experiment investigates the influence of message style and sidedness on consumer participation in green practices and explores the role of message usefulness and skepticism. Our results show that a narrative message style and a two-sided message increase perceived usefulness, reduce skepticism, and lead to greater behavioral intent. Further, the study supports the moderated serial mediation role of message usefulness and skepticism. These findings offer significant implications for businesses seeking to promote sustainable practices and engage consumers in green initiatives.